Uranium isotopes in ground and surface waters of Barreiro, Araxá, Minas Gerais State, Brazil - Mancini, Luis Henrique [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2015)
The isotope 234U is radiogenic and the decay chain from 238U through 234U proceeds as follows: 238U (4.46 Ga, ?) → 234Th (24.1 days, α) → 234Pa (1.18 min, α) → 234U (248 ka, α) → ... The isotopes 238U and 234U are in secular equilibrium in all minerals and rocks greater than one million years old and that are closed systems for U. The 234U/238U activity ratio (AR) is, therefore, unity in the bulk of such systems. However, rock/soilwater interactions frequently result in AR for dissolved uranium that is greater than unity. Alkaline rocks are found in southern Brazil in association with the Ordovician- Cretaceous sedimentary Paraná basin and mainly distributed along its margins. They vary considerably in age and composition, and have been assembled into distinct geographic provinces, such as the Alto Paranaíba Igneous Province, representing one of their most important ones, particularly due to the presence of economical deposits bearing niobium, phosphate, titanium and rare earth elements. The Alto Paranaíba Province includes the renowned carbonatite intrusion of Araxá, covering approximately 16 km2, which is in general related to a NW-trending linear structure bordering the São Francisco cratonic area and that is thought to be in evidence since late Precambrian times. The Araxá complex has been previously reported in literature as Barreiro, situated about 6 km distant from Araxá city, Minas Gerais State. It consists of a circular intrusion, 4.5 km in diameter, with the central part mainly formed by a carbonatite predominantly beforsitic in composition. A complex network of carbonatite as concentric and radial dykes quite variable in dimension and also small veins ranging from few millimeters to several centimeters in thickness are present intruding either alkaline or country rocks. Additional lithologies include mica-rich rocks, phoscorites and lamprophyres. All these rock types affect the chemical composition of ground and surface waters occurring at the Barreiro area like that of the well-known Dona Beija spring, which is characterized by possessing highly radioactive waters. This chapter reports the results of a U-isotopes radiochemical survey held at the Barreiro area, where several monitoring points for ground and surface waters have been sampled there in order to evaluate the environmental effects of their presence in solution.